Autonomy, relationality, and brain-injured athletes: a critical examination of the Concussion in Sport Group’s Consensus Statements between 2001 and 2023 - Michael McNamee (Sport, Ethics and Philosophy, 2024)
This article critically examines the development and consensus outputs of the Concussion in Sport Group. We examine the six Consensus Statements between 2001 and 2023 to explore the challenges that the presence of contextual forces pose to the development of effective and ethically justifiable medical guidelines to manage situations involving brain-injured athletes. First, we discuss the implicit and explicit ethical framework and goals underlining the statements. Secondly, drawing on a relational account of athlete choice, we expound on the limitations of the framework, concentrating on those resulting from a simplified understanding of athlete autonomy. Thirdly, we conclude by proposing a series of recommendations to improve concussion management protocols: (1) adopting a broader understanding of autonomy built upon relational accounts, beyond just the healthcare professional-athlete relationship; (2) further minimizing conflicts of interest that increase athletes’ vulnerability and hinder decision-making ability; (3) enhancing healthcare professional training to allow better adjustment of treatment plans to athletes’ contexts; and (4) promoting research on sociocultural elements affecting athletes’ vulnerability and autonomy.